EOP Demand in Industrial Corporations: A Stepping Stone to a Work Wonders ESP Teaching - Hapsari, Yulia (Fakultas Ilmu Budaya, Universitas Brawijaya, 2012)
The purpose of this research is to unearth the English for Occupational Purposes (EOP) demand in industrial corporations. The findings are then aimed at providing insight to schools and universities about EOP needed in workplace, so that schools and universities preparing qualified work power can create an effective ESP teaching. This research uses employees of some industrial corporations in Bontang, East Kalimantan as the subject of the research. It attends field observation, needs assessment, and needs analysis as the procedure. Data collected in this research are analyzed descriptively. In the field observation, present situation data picturing the situation of the present English for Specific Purposes (ESP) mastery of the research subjects are gathered. In order to do so, the researcher builds cooperation with one of prominent English courses in Bontang in which the research subjects study English. The teachers and manager of the English course are brought in as the sources of information to complete data gathered from an ESP classroom observation and personal experience. The teachers are interviewed and given a set of questionnaires related to the ESP classes and the research subjectsâ proficiency in English. Upon the data collection, the data are then inferred to find the problems related to the class.The needs assessment and needs analysis are aimed at revealing the needs of EOP in the industrial corporation. Therefore, the research subjects who are employees of some industrial corporations in Bontang as well as the personnel of Human Resource Department as the representative of the industrial corporation as the sponsor are taken as the subjects of the study to collect target needs data. The target needs data consist of information about the operatorsâ necessities, lacks and wants in learning English. To get the intended data, the research subjects are given a set of questionnaires and some of them are interviewed, while the personnel of the Human Resource Department of the industrial corporations are interviewed. Once the data are collected, they are grouped into the operatorsâ necessities, lacks, and wants. The needs analysis results on the findings that the research subjectsâ necessities in learning English is to be able to communicate orally about topics related to their job both in a casual conversation and in delivering a presentation. English is also used when they read manuals and journals, and write reports related to their job. It is also revealed that vocabulary mastery is the main problem, while improving their knowledge about English related to their job and improving their confidence in using English are their wants.Finally, an ESP syllabus containing general and specific objectives of the course, schema of the topics, and list of materials can be derived from the findings to provide a work wonders ESP teaching in schools and universities.Key Words: industrial corporations, ESP, EOP.